1986
DOI: 10.1159/000281181
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Exercise versus Surgery for Female Urinary Stress Incontinence

Abstract: Fifty consecutive female patients with genuine urinary stress incontinence were randomized either to surgery or to a pelvic floor training program. The operative procedure was chosen according to the type of bladder suspension defect on micturition cystourethrography. The training program was given 5 times in weekly lessons and the patients were guided by trained physiotherapists. Surgery was superior to the pelvic floor training program both subjectively and objectively. However, a significant improvement was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
5

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 7 publications
1
70
0
5
Order By: Relevance
“…Extended follow-up up to 4-8 years showed that everybody in this group was satisfied with their improvement. 13 In present study 84.1% SUI patients felt improvement. Pelvic floor exercise is least invasive and without any undesirable side effects, which leads to either improvement or complete cure of SUI in 80-85% of cases.…”
Section: Discussionsupporting
confidence: 51%
“…Extended follow-up up to 4-8 years showed that everybody in this group was satisfied with their improvement. 13 In present study 84.1% SUI patients felt improvement. Pelvic floor exercise is least invasive and without any undesirable side effects, which leads to either improvement or complete cure of SUI in 80-85% of cases.…”
Section: Discussionsupporting
confidence: 51%
“…A similar persisting effect has been reported following other noninvasive treatment modalities such as electrostimulation or phys iotherapy [11,12]. However, whether the medical treat ment per se is responsible for the curative effect, possibly due to re-education [ 11 ], is difficult to assess.…”
Section: Discussionmentioning
confidence: 55%
“…As it is an invasive treatment and has complications like bleeding, pelvic pain and difficulties of micturition, t h e p a t i e n t s a n d p h y s i c i a n s t e n d t o w a r d conservative treatment modalities 9 ) . Drugs, hormonal replacement therapy, mechanical support devices, rehabilitation of pelvic floor and electrical stimulation are some of the treatment alternatives to surgery 10) .…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent voluntary contractions can be seen after optimal application of Kegel exercises 7) . But its cure rate was reported as 12-13% and the number patients refusing to continue treatment is quiet high 9,11) . Biofeedback is a method which increases the success of Kegel exercises by making the patients sense the contractions using audio or visual devices 12) .…”
Section: Discussionmentioning
confidence: 99%